2009
DOI: 10.1002/cyto.b.20470
|View full text |Cite
|
Sign up to set email alerts
|

Absolute CD4+ cell count using a plastic microchip and a microscopic cell counter

Abstract: We have designed and evaluated the performance of a simple, rapid, and affordable method for counting CD41 T-cells with the use of plastic microchips. This new system is an adaptation of a ''nolyse, no-wash,'' volumetric single platform assay, and absolute CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…A recent study showed similar performance to flow cytometry in an HIV infected cohort [27]. Furthermore, a separate study showed that T cells can be distinguished from monocytes based on their different intensity after staining with fluorescent anti-hCD4 [28]. The CD4 counts from this microchannel method correlate closely with results of flow cytometry in 100 specimens, but blood dilution and staining are yet to be automated.…”
Section: The Need For Point Of Care Technologiesmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent study showed similar performance to flow cytometry in an HIV infected cohort [27]. Furthermore, a separate study showed that T cells can be distinguished from monocytes based on their different intensity after staining with fluorescent anti-hCD4 [28]. The CD4 counts from this microchannel method correlate closely with results of flow cytometry in 100 specimens, but blood dilution and staining are yet to be automated.…”
Section: The Need For Point Of Care Technologiesmentioning
confidence: 91%
“…In addition to being single platform and potentially portable, imaging cytometry detects a large number of cells simultaneously, while FACS measures one cell at a time. Of the several imaging systems described in this section above, detection of the sandwich structures has a higher accuracy by eliminating monocyte interference [25,26,29,33], while label-free imaging of all cells captured by a single antibody [28,34โ€“37] offers greater operation simplicity and faster turn-around time. The field performances of these systems are yet to be established to determine if the strength of each system outweighs its shortcomings.…”
Section: The Need For Point Of Care Technologiesmentioning
confidence: 99%
“…Some designs relied on the even distribution of cells in a plastic chamber to produce accurate counts [80]. Others have used a microfabricated membrane to filter out erythrocytes, leaving leukocytes, which were fluorescently labeled [81].…”
Section: B Global Health Solutions 1) Optical Methodsmentioning
confidence: 99%
“…The new cell viability test was developed by modifying (or improving) the previously reported microscopic technique for counting residual WBC with microchannel chip 3, 4. The microchannel chip was made with polymethylmetacrylate (PMMA).…”
Section: Methodsmentioning
confidence: 99%